The Role Of Chlorhexidine In Dentistry: Mechanisms Of Action And Clinical Applications - Anindia Nazla Kusumaputri; Shahnaz Fitri Rahmadhanna; Gema Gempita (International Journal of Health Engineering and Technology, 2026)
This literature review discusses the role of chlorhexidine as an antiseptic in dentistry, where it is still regarded as the gold standard for use. Chlorhexidine is a cationic bisbiguanide compound with broad-spectrum antimicrobial activity against Gram-positive and Gram-negative bacteria. It acts by interacting with the microbial cell membrane, producing a bacteriostatic effect at low concentrations and a bactericidal effect at higher concentrations. In clinical practice, chlorhexidine is available in various formulations, including mouthwash (0,12-0,2%), gel (0,12-1%), 2% irrigating solution, and higher-concentration varnish, which are selected according to therapeutic needs. Its applications include caries control through the reduction of Streptococcus mutans, periodontal therapy as an adjunct to scaling and root planing, support in endodontic treatment as an alternative irrigant, and post-surgical care to reduce the risk of complications such as alveolar osteitis. Chlorhexidine has been proven effective, its use should be limited due to potential side effects, including tooth staining, taste alteration, and xerostomia; therefore, it is recommended as an adjunctive therapy based on specific clinical indications.